End-to-end QOS management of compressed video streams - See, Shu Wei. (2008)
There has been an increased interest in adaptive video quality control for end-to-end Quality of Service (QoS) management for the transportation of compressed video streams. One approach is to dynamically adjust the output video bit rate based on the status of the network determined by feedback analysis. The goal of this thesis is to investigate a perceptual video quality feedback mechanism for adaptive transmission rate control of a video stream which is multicast to a heterogeneous group of receivers in a videoconferencing application.